Hakikat Kurikulum Dalam Kurikulum Pendidikan Islam - Nabila Alifah; Rina Ramadhani; Alihan Satra (Advances In Education Journal, 2025)
The Islamic Education Curriculum serves as a fundamental framework for shaping learners who excel academically while possessing strong moral character, spiritual resilience, and adaptability to contemporary challenges. In Islamic thought, the curriculum is understood as an integrated system of planning, implementation, and evaluation aimed at forming Muslims who are faithful, knowledgeable, and virtuous. The Qur’an and Hadith function as normative sources that require contextual interpretation to remain relevant in modern educational settings. Islamic education emphasizes the integration of cognitive development with moral and ethical values, positioning learning as a process of holistic character formation. This curriculum adopts a comprehensive approach that balances spiritual objectives, moral conduct, intellectual growth, and essential life skills. The integration of Islamic values with general sciences requires contextual and value-based pedagogical strategies rather than rote memorization. However, implementation faces challenges such as limited teacher competence and a lack of contextual teaching materials. Therefore, strengthening teacher capacity and developing adaptive learning resources are essential. As noted by Irmawati (2024), Islamic value integration must respond to contemporary social and technological demands to holistically develop students’ knowledge, skills, and moral attitudes.